STUDY OF PATHOMORPHOLOGICAL CHANGES IN THE PLACENTA AT 11-12 WEEKS OF PREGNANCY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article discusses research in the field of classical morphological descriptions of the early development of the placenta. When morphologically studying the placenta, according to an analysis of a large amount of literature, before the ninth week of pregnancy, a restriction of arterial communication with the villous space is detected, which leads to low oxygen tension in the placenta. However, in the ninth week, there is a weakening of the arterial plugs, increasing the flow of oxygen to the placenta. Studies have also shown that replacing plasma protein-A with placental growth factor in screening for fetal trisomy and preeclampsia may improve screening accuracy. Taken together, these studies contribute to the understanding of early placental development and the factors influencing its normal functioning.